Trends in Digital Marketing Research: Bibliometric Analysis for 2019 – 2023 - Andriansyah, Andriansyah; Anshori, Mochammad; Andiyani, Nurita (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Digital Marketing (DM) is an important aspect in an industry, especially in the digital era. This study aims to analyze publication trends related to DM, technological innovation, and environmental aspects in the last five years 2019-2023 using bibliometric analysis. Data taken from the Scopus database was refined into 218 publications. The trend of DM-related publications related to technological innovation and sustainability has increased significantly in the last five years, and the most publications will occur in 2023, reaching 79 documents. The trend of the most published sources is Sustainability with a total of 23 published articles. Network cluster analysis identified six main research focuses: The relationship of DM and marketing strategy, digital transformation, social media, big data, sustainability, and the role of DM in Covid-19. The implication is that DM is still a central issue in the business world, while marketing strategies need to continue to adapt their digital marketing strategies to dynamic changes in the business sphere, paying attention to aspects of technological innovation, consumer behavior and sustainability in order to be able to read maps of market trends and consumer interests to achieve maximum goals.